Towards Sustainable Transport Planning in the United States - Ramani, Tara; Zietsman, Josias; Ridley Pryn, Marie (European Journal of Transport and Infrastructure Research, 2018)
This paper provides an analysis of how sustainability concepts are currently addressed within the broad framework of surface transportation planning in the United States (US). We first discuss the overall transportation planning process in the US, and the role of key agencies and actors. This is followed by a brief assessment of how sustainability is addressed as part of national policies and programs. We then present a case study of the US Federal Highway Administration’s INVEST (Infrastructure Voluntary Evaluation Sustainability Tool), and its application by four agencies. In general, the findings indicate that there is acknowledgement of triple bottom line sustainability considerations in transportation planning – though a cohesive and unified approach is lacking. We also note the presence of planning initiatives and discourse that implicitly address sustainability issues, by targeting related considerations such as liveability, health, climate adaptation, quality of life, and economic opportunity.